A case of multiple sclerosis with negatively converted anti‐natalizumab antibodies. Issue 4 (29th May 2020) - Miyamoto, Katsuichi; Kusunoki, Susumu
Abstract: Background: The therapeutic effect of natalizumab, a disease‐modifying drug for multiple sclerosis (MS), may be decreased in the presence of neutralizing antibodies. In particular, if the neutralizing antibody is persistently positive, the treatment must be stopped. We experienced a case in which anti‐natalizumab antibodies were persistently positive but then negatively reversed during the course of treatment. Case presentation: The case is a 38‐year‐old female MS patient. After three attacks of MS, she was treated with dimethyl fumarate, but the relapse continued. Anti‐JC virus titer of her serum was more than 2.5, but she selected to treatment with natalizumab. At her initial treatment, she had allergic symptoms and was found to be positive for anti‐natalizumab antibodies. In the second treatment, she received an infusion after taking antiallergic drugs, after which her allergic symptoms reduced. Thereafter, she received natalizumab treatment in the same manner. Two months later, reexamination of the anti‐natalizumab antibodies was persistently positive. However, she decided to continue natalizumab because there were no recurrences. Two years after the start of natalizumab treatment, the anti‐natalizumab antibodies were found to be negatively inversed. Because anti‐JC virus antibody remained elevated, she decided to continue the treatment with natalizumab by dosing intervals every 6 weeks. Thereafter, no recurrence was observed. Conclusions: Even if the neutralizing antibodies against natalizumab are positive, treatment continuation may be considered if the therapeutic effect is certain and the side effects are within the allowable range. Abstract : A rare case in which the persistent positive anti‐natalizumab antibody was reversed. If the side effects are within an acceptable range and the therapeutic effect is clear, we may consider continuing treatment with careful observation.